2015
DOI: 10.17645/si.v3i3.201
|View full text |Cite
|
Sign up to set email alerts
|

The Processes of Inclusion and Exclusion in Physical Education: A Social-Relational Perspective

Abstract: Existing research on inclusion and exclusion processes in physical education (PE) has particularly focused on exclusion from PE as something being done to students and attributed to specific social categories such as (female) gender, (low) physical skills or (minority) ethnic background. This article aims to develop a social-relational perspective on inclusion and exclusion processes defined as students' participation or non-participation in PE interpreted as a community of practice. In so doing, the article e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…Flintoff and Fitzgerald (2012, 16) captured the extent of this challenge in stating that the physical education profession appears 'ill-equipped to acknowledge, celebrate and plan for difference'. Other research supports their stance, pointing to the apparent failure of teachers and teacher educators to challenge the deep-rooted historical practices that exist within the subject (Grimminger 2014;Munk and Agergaard 2015). This is despite research that has provided clear insights into the exclusionary nature of physical education, with studies highlighting that in many instances physical education is structured and delivered in ways that establish and maintain exclusionary discourses, while continuing to privilege individuals who are white , masculine (Brown and Evans 2004) and of high sporting/motor-skill ability (Fitzgerald 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Flintoff and Fitzgerald (2012, 16) captured the extent of this challenge in stating that the physical education profession appears 'ill-equipped to acknowledge, celebrate and plan for difference'. Other research supports their stance, pointing to the apparent failure of teachers and teacher educators to challenge the deep-rooted historical practices that exist within the subject (Grimminger 2014;Munk and Agergaard 2015). This is despite research that has provided clear insights into the exclusionary nature of physical education, with studies highlighting that in many instances physical education is structured and delivered in ways that establish and maintain exclusionary discourses, while continuing to privilege individuals who are white , masculine (Brown and Evans 2004) and of high sporting/motor-skill ability (Fitzgerald 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Munk and Agergaard (2015) noted that research has focused on exclusion as 'something being done' to students and has been directed towards social categories such as gender, physical skills and minorities. In contrast to searching for exclusion based on groups, Munk and Agergaard (2015) investigated the complex interactions within a group of students and found that students' lack of physical skills and necessary social relationships might lead to exclusion in activities. We acknowledge that categories such as gender, physical skills, social relationships and minorities may influence social inclusion and exclusion in activities in PE.…”
Section: Social Inclusion In Pementioning
confidence: 99%
“… Hill (2015b) argues that student status in PE contexts is often associated with performance of highly proficient sporting bodies, and certain bodily appearance and performance, such as ability, strength, or muscularity, attain high status. Research shows that students are excluded from PE because they do not have the physical skills to gain legitimacy from other students ( Munk and Agergaard, 2015 ). Using interviews, Hill (2015b) shows how boys invested in their bodies by doing physical activities that enabled them to develop muscularity and fitness in PE.…”
Section: Introductionmentioning
confidence: 99%